Revitalisasi Pengembangan Moderasi Beragama Serta Urgensinya dalam Meningkatkan Minat Beragama di Kelurahan Sayur Matinggi, Kecamatan Batang Onang, Kabupaten Padang Lawas - Triase Triase; Agus Prianto Siregar; Gery Syahputra Harahap; Pipi Darsina Siregar; Zakiah Nur Harahap (MODELING: Jurnal Program Studi PGMI, 2023)
Revitalization is an effort made to regrow something that has been extinguished or dim that previously existed. While religious moderation is about how to view, behave, and practice religious teachings properly without coercion, intimidation, and violence. The era that continues to experience development and progress in various aspects coupled with increasingly sophisticated technological advances, makes all related information more easily accessible anywhere and anytime, consciously or not, gradually creating a shift in values ​​towards the culture and traditions of the nation, especially religious people. The country of Indonesia, which is known as a country with diverse cultures, customs, ethnicities, races and languages, has a good image in the eyes of the world, which is related to manners and manners. This is all delivered by the understanding of the people who are able to be moderate in carrying out social and religious life. This research is presented to provide information regarding the importance of revitalizing religious moderation in people's lives where later this can lead to increased public interest in religion, especially in Sayur Matinggi Village, Batang Onang District, Padang Lawas Regency. This study uses a qualitative method with a descriptive approach, where the research data is obtained from observations, interviews and also documentation. While the data that has been obtained is analyzed by reducing, presenting the data and then drawing conclusions